Post-traumatic stress disorder (ptsd) and inadaptation in women victims by domestic violence in the marital relationship according to the age - Huerta Rosales, Rosa Elena (2014)
The domestic violence is a very big social problem, because of its high frequency and seriousness of the facts, and also its negative effects against the real victims and the close friends and relatives. In the study, the variables of post-traumatic stress disorder and inadaptation were analyzed according to age in a sample of 256 female victims of domestic violence in the marital relationship, who were administered a sociodemographic data file, severity scale of posttraumatic stress disorder symptoms, the inadaptation scale and a scale of somatic symptoms of anxiety. It was found a relevant correlation between the PTSD and inadaptation according to the age in the different age groups. In the same way, a very important correlation among each one of post-traumatic stress disorder components: reexperimentation, avoiding, and activation with the inadaptation in all kinds of age groups. It is observed that the somatic performance of anxiety, related to the domestic violence, apart from de age, has a significative relationship with the inadaptation. On the other hand, it was found that the chronological age is a variable that does not point out in the post-traumatic stress disorder symptom nor the inadaptation behavior. It is the violence situation that determines and produces the disorders in the woman’s mental health, which is observed in the obtained mean values that result being more than the means of the cut stocking.